Fixed Point Properties of Decomposable Isotone Operators in Posets - Diviccaro, Maria Luigia (Sarajevo Journal of Mathematics, 2024)
A known theorem of R. M. Dacić, involving increasing operators decomposable into a finite product of monotone mappings, is extended from a complete lattice to a poset by using our previous results. 2000 Mathematics Subject Classification. 47H10